Impact of stocking rate on species diversity and composition of a subtropical grassland in Argentina - Pizzio, Rafael Mario; Herrero Jáugueri, Cristina; Pizzio, Mariano; Oesterheld, Martin (Wiley, 2019)
Questions: What is the effect of a range of controlled stocking rates on plant species richness and diversity? Location: Subtropical grasslands of Corrientes, Argentina, South America. Methods: We studied the effect of three controlled stocking rates (0.6, 0.8 and 1.0 cow equivalents·ha−1) on species diversity and composition during 8 yr. We calculated species diversity using the antilog of the Shannon‐Wiener index, and considered its two components, richness and evenness. We also assessed the proportion of prostrate and erect species. Species abundance was based on biomass estimations. Results: Species diversity under high stocking rates gradually decreased throughout the experiment and became nearly 50% lower than under low stocking rate. This decline was largely accounted for by changes of evenness because species richness was not affected by stocking rates. Species composition clearly diverged among the three treatments over time. Low stocking rate maintained a fairly constant relative cover of erect and prostrate grasses throughout the experiment, whereas intermediate and high stocking rate treatments were gradually and consistently enriched in prostrate grasses and forbs. These effects occurred simultaneously with drastic inter‐annual changes likely driven by annual precipitation. Conclusions: The range of stocking rates had no effect on species richness, but reduced diversity through the effect on evenness. High stocking rate progressively increased the proportion of prostrate species in the biomass.